Ethyl 1-(butan-2-yl)-2-(2-methoxyphenyl)- 1H-benzimidazole-5-carboxylate - Natarajan, Arumugam; Ngah, Nurziana; Osman, Hasnah; Abdul Rahim, Aisyah Saad (Wiley-Blackwell Publishing, Inc., 2011)
In the title compound, C21H24N2O3, the mean planes of the benzene ring and the benzimidazole ring system form a dihedral angle of 69.94 (7). The ethyl group atoms of the ethanoate fragment are disordered over two sets of sites, with refined occupancies of 0.742 (6) and 0.258 (6). In the crystal,there are weak C—H N hydrogen bonds which connectmolecules into chains along the b axis. A weak intermolecular C—H interaction is also observed.